2017
DOI: 10.1038/srep40032
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of changes in structure and thermodynamic of spruce budworm antifreeze protein under subfreezing temperature

Abstract: The aim of this theoretical work is to investigate of the changes in structure and thermodynamics of spruce budworm antifreeze protein (sbAFP) at low temperatures by using molecular dynamics simulation. The aqueous solution will form ice crystal network under the vaguely hexagonal shape at low temperature and fully represented the characteristics of hydrophobic interaction. Like ice crystal network, the cyclohexane region (including cyclohexane molecules) have enough of the characteristics of hydrophobic inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Hence, this occurrence holds signi cant potency as a result of the hydrogen bonds formed between the ice/water and the residues, ultimately dictating the effectiveness of the antifreeze proteins' functionality (Duboue and Laage 2014). Moreover, the prevention of ice formation relies on the presence of AFP covering the surface of the ice interface that is exposed to water (Nguyen and Le 2017). The IBS in AFPs has been acknowledged as being hydrophobic and made up of numerous hydrogen bonds (Garnham et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, this occurrence holds signi cant potency as a result of the hydrogen bonds formed between the ice/water and the residues, ultimately dictating the effectiveness of the antifreeze proteins' functionality (Duboue and Laage 2014). Moreover, the prevention of ice formation relies on the presence of AFP covering the surface of the ice interface that is exposed to water (Nguyen and Le 2017). The IBS in AFPs has been acknowledged as being hydrophobic and made up of numerous hydrogen bonds (Garnham et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, through molecular dynamics simulation, it has been observed that the hydrophobic IBS within AFPs rearranges water molecules into a structure resembling ice. (Nguyen and Le, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For ice-active proteins these effects could be more pronounced because studies of INPs and related AFP β-helices have shown that for this class of proteins all of these factors are affected by temperature. For example, it has been shown that their hydration 52 and lateral protein interactions 53 change significantly when decreasing the temperature close to the water melting point. The protein–water interface of INPs has also been observed to become less dynamic at lower temperatures 28 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of INpros and related AFP β-helices have shown that all these factors can be affected by temperature changes. For example, it has been shown that hydration 57,58 and lateral protein interactions 58 change significantly when lowering the temperature close to the water melting point. The protein-water interface has also been observed to become less dynamic at lower temperatures.…”
Section: Resultsmentioning
confidence: 99%